1909 N.D. Laws 203, ch. 165, § 1 - (:unkn) unknown (General Publisher, 1909)
No body of men, other than the regularly organized corps of the national guard and militia and the troops of the United States, shall associate themselves together as a military company or organization, or parade in public with firearms in any city or town of this state.
--
Keywords: MILITIAS